The Evaluation of Lighting System Planning based on Green Building Concepts using DIALux Evo Software - Rosyad Febrian, Muhammad Dziya'ur; Pravitasari, Deria; Kurniawan, Andriyatna Agung; Setiawan, Hery Teguh (Jurnal Listrik, Instrumentasi, dan Elektronika Terapan, 2026)
Building construction contributes to 40% of carbon emissions, while during the operational phase, approximately 50% of energy is used to create an artificial climate, such as lighting systems. This study applies the Green Building concept to the lighting system on the first floor of Building X with the aim of achieving energy savings and reducing carbon emissions. The scope of the study includes the evaluation and improvement of the lighting system design on the first floor of Building X based on Green Building standards in accordance with Minister of Public Works and Public Housing Regulation No. 21 of 2021. The evaluation results show that the lighting system on the first floor of Building X does not fully meet Green Building standards, therefore improvements are needed. Improvements to the artificial lighting system were made by recalculating the lighting requirements, resulting in a 16.62% reduction from the initial plan. Meanwhile, improvements to natural lighting by combining it with artificial lighting resulted in a reduction of up to 61.28%. Therefore, the first floor of Building X supports one of the principles of the Green Building concept, which is the reduction of energy use and carbon emissions.